Nickel-coated graphite doped FeCoNi oxygen evolution coating catalyst and preparation method thereof

The coating is prepared by the nickel-covered graphite-doped FeCoNi oxygen evolution coating catalyst using atmospheric plasma spraying technology, which solves the problem of slow kinetics of the anode oxygen evolution reaction, and achieves efficient OER performance and stability.

CN119433595AActive Publication Date: 2025-02-14SHENYANG UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411414507.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-14
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the existing electrocatalytic hydrogen production process, the kinetics of the anode oxygen evolution reaction (OER) are slower, and the low reserve amount and high cost of precious metal catalysts limit their wide application.

Method used

The coating was prepared by atmospheric plasma spraying technology using a nickel-clad graphite-doped FeCoNi oxygen evolution coating catalyst to control the atomic ratio of Ni3C in FeCoNi powder to adjust the number of pores on the coating surface, and improve the specific surface area and OER performance of the catalyst.

Benefits of technology

High OER performance and stability are achieved, the coating is well bound to the metal substrate, the porosity reaches 22%, providing more active sites and promoting electrocatalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433595A_ABST
    Figure CN119433595A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electro-catalysis oxygen evolution coatings, and particularly relates to a nickel-coated graphite doped FeCoNi oxygen evolution electro-catalyst and a preparation method thereof, the preparation method comprises the steps of ball milling powder mixing, surface degreasing, sand blasting roughening and plasma spraying, and a FeCoNi-Ni3C oxygen evolution coating catalyst is prepared. The prepared coating is well combined with a metal substrate, the atmosphere plasma spraying technology enables the coating to be well combined with the substrate, and the structure of the coating is not changed before and after a stability test. Besides, due to the characteristics of the APS technology, the prepared coating contains a certain content of unmelted or semi-melted metal elementary substances of Fe, Co and Ni, and due to the characteristic, metal elements in the coating tend to move towards higher binding energy during electrochemical testing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic oxygen evolution coatings, in particular to a nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst and a preparation method thereof. Background Art

[0002] Hydrogen production by water electrolysis has the advantages of wide sources and no pollution, making it an ideal hydrogen production process. However, the slow kinetics of the anode oxygen evolution reaction (OER) has greatly restricted the current development of water electrolysis technology. Catalysts based on precious metals such as Pt, Ru, and Ir have been shown to have excellent HER performance, but are limited by the low reserves and high application costs of precious metals, making it difficult for them to become ideal electrocatalysts for the popularization of electrocatalytic hydrogen production processes. It is known that increasing the surface area of ​​a catalyst can promote its reaction rate. Therefore, preparing catalysts with different porosities by adjusting the surface morphology of the catalyst is considered to be a feasible method.

[0003] Coated catalysts have high economic efficiency. The use of atmospheric plasma spraying (APS) technology to prepare the coating can produce certain pores on the surface of the coating, increase active sites, and promote the process of electrocatalytic reaction. In addition, among various three-dimensional metal catalysts, oxides or hydroxides of Fe, Co, and Ni show excellent OER potential and activity, which is mainly due to the high reserve content and theoretical high catalytic properties of these three metals. This patent uses APS technology to prepare coated catalysts, and controls the number of pores on the surface of the coating by controlling the atomic ratio of Ni3C in FeCoNi powder. C can play a supporting role in the coating and stabilize the coating structure. It can also interact with the metal in the coating to inhibit the oxidation of the metal elements in the coating. At the same time, the synergistic effect between Fe, Co, and Ni can improve the OER performance of the coating.

[0004] Invention patent CN117604554A The present invention discloses a method for preparing an electrocatalytic water decomposition catalyst based on FeCo-P. The preparation method uses FeCoMOF-74 as a precursor and then obtains FeCo-P by high-temperature phosphating. The FeCo-P prepared by the present invention can efficiently realize electrocatalytic full water decomposition; however, its preparation process is cumbersome, has high temperature requirements, and has a long preparation cycle.

[0005] Invention patent CN118390096A The present invention provides a high-performance Co-NC oxygen evolution catalyst and a preparation method thereof, which belongs to the field of oxygen evolution electrocatalysis technology, and is a catalyst composed of a CoNx active center part and nitrogen-doped carbon co-loaded on a carbon material. The method is: γ-cyclodextrin (cyclic oligosaccharide family) and cobalt salt are mixed in a liquid phase, and Co@MOF is obtained by a solution method. Subsequently, Co@MOF is mixed with a nitrogen source (dicyandiamide), placed in a protective atmosphere, and a Co-NC catalyst is obtained after high-temperature heating. The oxygen evolution overpotential of the oxygen evolution catalyst prepared by this process is higher than that of commercial IrO2, and the overpotential is improved compared to many current catalysts, but there is still a lot of room for improvement compared to noble metal-based catalysts.

[0006] From the above prior art, it can be seen that great efforts have been made in various fields to improve the HER or OER performance of transition metal-based (TM) catalysts. TM-based compound catalysts in the past decade include oxides, carbides, (oxy)hydroxides, etc. Among them, TM-based (oxy)hydroxides have attracted great attention in OER due to their easily adjustable three-dimensional electronic structure and satisfactory electrocatalytic performance. However, at higher current densities, the activity and durability of this catalyst are poor. It is known that exposing more active sites by adjusting the morphology of the catalyst is considered to be an extremely effective and highly economical method. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst and a preparation method thereof.

[0008] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0009] One of the objects of the present invention is to provide a method for preparing a nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst, comprising the following steps:

[0010] S1. Mixing FeCoNi powder and nickel-coated graphite Ni3C powder and then ball milling to obtain FeCoNi-Ni3C powder, wherein the atomic ratio of Ni3C in the FeCoNi-Ni3C powder is 25% to 75%;

[0011] S2, using sodium hydroxide alkaline cleaning solution to remove oil stains on the surface of the metal substrate, and then using ultrasonic cleaning;

[0012] S3, sandblasting the surface of the metal substrate until the roughness of the surface of the metal substrate is Ra5.5μm~Ra6.5μm;

[0013] S4. Plasma spraying is performed on the surface of the metal substrate after sandblasting using FeCoNi-Ni3C powder to obtain a FeCoNi-Ni3C oxygen evolution coating catalyst with a thickness of 400 to 500 μm.

[0014] The principle of the present invention is: iron, cobalt and nickel are three metals with wide sources, low prices, and close performance to precious metals Pt and Ir in the free energy volcano diagram, and are considered to be ideal substitutes for precious metal catalysts. The FeCoNi coating prepared by atmospheric plasma spraying technology was found to have a certain number of pores distributed on its surface under a light microscope. These pores can increase the specific surface area of ​​the catalyst to a certain extent, thereby providing more active sites to promote electrocatalytic reactions. At the same time, the synergistic effect between the three metal elements of FeCoNi will also promote OER reactions. From the perspective of electronegativity, the electronegativity of Ni is about 1.91, which is between Fe (about 1.83) and Co (about 1.88). The higher electronegativity of Ni means that it can play a role in adjusting the overall electronic environment, promoting the redistribution of electrons in the Fe-Co-Ni alloy, and then affecting the electron density on the catalyst surface. Appropriate electronic structure adjustment helps to optimize the adsorption capacity of the catalyst, thereby improving the catalytic activity. On the one hand, the doping of Ni3C can adjust the surface morphology of the coating, increase the porosity of the coating, thereby exposing more active sites, and the Ni-rich coating will also have a certain promoting effect on the oxygen evolution process; on the other hand, the C element can promote electron transfer and stabilize the coating structure.

[0015] Furthermore, in step S1, glass balls are used for ball milling, the diameter of the glass balls is 4 mm-10 mm, the ball-to-powder ratio is 4:1, the ball mill speed is 1200 rad / min-1600 rad / min, and the ball milling time is 18 h-22 h.

[0016] Furthermore, in the step S1, the particle size of the FeCoNi powder is 300-400 mesh, and the powder is a spherical powder; the particle size of the nickel-coated graphite Ni3C powder is 300-400 mesh, and the powder is a flake powder.

[0017] Furthermore, the metal substrate is one of copper, copper alloy, aluminum, aluminum alloy, and stainless steel.

[0018] Furthermore, in the step S2, the mass percentage of the sodium hydroxide alkaline washing solution is 4.0% to 5.0%, and the metal substrate is immersed for 3.0 min to 5.0 min at a temperature of 60° C. to 70° C. to remove oil stains on the surface of the metal substrate.

[0019] Furthermore, in step S3, the surface of the metal substrate is sandblasted using white corundum abrasive particles of 180-200 mesh, the sandblasting angle is 75°-85°, the pressure of the compressed air is 0.56MPa-0.60MPa, and the sandblasting distance is 80mm-110mm.

[0020] Furthermore, in step S4, the plasma spraying process parameters are: welding current 650A~700A, voltage 42V~45V; spraying speed is 1800mm / min~2000mm / min, spraying distance is 150mm~180mm, powder output of powder feeding pipe is 10mg / s-15mg / s, powder feeding machine speed is 0.55rad / min~0.7rad / min, powder feeding gas is argon, powder feeding gas flow rate is 38psi~42psi, shielding gas is argon, shielding gas flow rate is 42psi~46psi, combustion-supporting gas is hydrogen, and gas flow rate is 8psi~12psi.

[0021] The second object of the present invention is to provide a nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst prepared by the above method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The coating prepared by the present invention is well bonded to the metal substrate, and the atmospheric plasma spraying technology can make the coating and the substrate well bonded. The structure of the coating does not change before and after the stability test. In addition, due to the characteristics of the APS technology itself, the coating prepared by the invention contains a certain amount of unmelted or semi-melted Fe, Co and Ni metal elements. This characteristic can make the metal elements in the coating have a tendency to move to a higher binding energy during the electrochemical test.

[0024] When the atomic ratio of Ni3C in FeCoNi-Ni3C is 50%, the overall porosity of the coating can reach 22%. This feature ensures that the coating can provide a larger surface area and more active sites to promote OER performance during electrochemical measurements. On the one hand, the C element stabilizes the overall structure of the coating with a larger porosity, and on the other hand, it can promote electron transfer during the electrochemical process. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The microscopic morphology of the FeCoNi-Ni3C oxygen evolution coating catalyst under an electron microscope before the oxygen evolution reaction in Example 1 of the present invention and the porosity of the coating calculated based on the microscopic morphology of the FeCoNi-Ni3C oxygen evolution coating catalyst before the oxygen evolution reaction are shown in FIG.

[0026] Figure 21 is a linear sweep voltammetry (LSV) curve of the FeCoNi-Ni3C oxygen evolution coating catalyst before and after the stability test in Example 1 of the present invention;

[0027] Figure 3 It is the double layer capacitance (Cdl) of the FeCoNi-Ni3C oxygen evolution coating catalyst in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0029] Example 1

[0030] 1) Ball milling powder mixing: In a stainless steel crucible, FeCoNi powders of equal molar ratio are mixed with nickel-coated graphite (Ni3C) powders, wherein FeCoNi is spherical powder and nickel-coated graphite (Ni3C) is flaky, and the particle size of the two powders is 400-500 mesh. Glass balls are used for ball milling, and the diameter of the glass balls is 4mm-10mm. The ball mill speed is 1200rad / min, and the ball milling time is 20h to obtain FeCoNi-Ni3C powders, and the atomic ratio of Ni3C in FeCoNi-Ni3C powders is 50%.

[0031] 2) Surface degreasing: Use sodium hydroxide alkaline cleaning solution to remove oil stains on the surface of the metal substrate; the mass percentage of the sodium hydroxide alkaline cleaning solution is 5.0%, and the temperature is 60°C, and the immersion time is 5.0 minutes. The metal substrate is a 100mm×100mm copper plate (brand T2) with a thickness of 2mm.

[0032] 3) Sandblasting: Use 180-200 mesh white corundum abrasive to sandblast the surface of the copper plate. The sandblasting angle is 75°-85°, the pressure of compressed air is 0.56 MPa, and the sandblasting distance is 100 mm, until the surface appears a silver-gray rough luster; the surface roughness of the copper plate after sandblasting is Ra6.0 μm. After sandblasting, use compressed air to blow away the sticky sand on the surface.

[0033] 4) Plasma spraying: The ball-milled FeCoNi-Ni3C powder was sprayed on the surface of the copper plate after sandblasting roughening. The plasma spraying process parameters were: welding current 700A, voltage 43V, FeCoNi-Ni3C oxygen evolution coating catalyst thickness 420μm; the spraying speed of the FeCoNi-Ni3C oxygen evolution coating catalyst was 1800mm / min, the spraying distance was 160mm, the powder output of the powder feeding pipe was 12mg / s, the powder feeding machine speed was 0.65rad / min, the powder feeding gas was argon, the powder feeding gas flow rate was 40psi, the shielding gas was argon, the shielding gas flow rate was 46psi, the combustion-supporting gas was hydrogen, and the gas flow rate was 10psi; before plasma spraying, the metal powder for plasma spraying was preheated and dried in a drying box, the drying temperature was 70°C, and the drying time was 1h.

[0034] Example 2

[0035] The atomic ratio of Ni3C in the FeCoNi-Ni3C powder is 25%, and the rest is the same as in Example 1.

[0036] Example 3

[0037] The atomic ratio of Ni3C in the FeCoNi-Ni3C powder is 75%, and the rest is the same as in Example 1.

[0038] Comparative Example 1

[0039] The atomic ratio of Ni3C in the FeCoNi-Ni3C mixed powder is 0%, and the prepared coating is an original coating with an equal molar ratio of FeCoNi.

[0040] The specific operation steps of the prepared oxygen evolution catalyst coating are as follows:

[0041] 1) Surface degreasing: Use sodium hydroxide alkaline cleaning solution to remove oil stains on the surface of the copper plate; the mass percentage of the sodium hydroxide alkaline cleaning solution is 4.0%, and the immersion time is 5.0 min at a temperature of 60°C.

[0042] 2) Sandblasting: Use 180-200 mesh white corundum abrasive to sandblast the surface of the copper plate. The sandblasting angle is 75°-85°, the pressure of compressed air is 0.56 MPa, and the sandblasting distance is 80 mm, until a silver-gray rough luster appears on the surface. The surface roughness of the copper plate after sandblasting is Ra5.5 μm. After sandblasting, use compressed air to blow away the sticky sand on the surface.

[0043] 3) Plasma spraying: FeCoNi spherical alloy powders of equal molar ratio were sprayed on the surface of the copper plate after sandblasting roughening. The plasma spraying process parameters were: welding current 650A, voltage 42V, FeCoNi alloy coating thickness 450μm; the spraying speed of the FeCoNi alloy coating was 2000mm / min, the spraying distance was 150mm, the powder output of the powder feeding pipe was 12mg / s, the powder feeder speed was 0.6rad / min, the powder feeding gas was argon, the powder feeding gas flow rate was 40psi, the shielding gas was argon, the shielding gas flow rate was 44psi, the combustion-supporting gas was hydrogen, and the gas flow rate was 8psi; before plasma spraying, the metal powder for plasma spraying was preheated and dried in a drying box, the drying temperature was 70°C, and the drying time was 2h.

[0044] In order to test the performance of the catalyst, the copper plates after plasma spraying of Examples 1 to 3 and Comparative Example 1 were cut into standard test blocks of 10 mm × 5 mm × 2 mm using a wire cutting device (DK7720). The coating surface of the cut sample was polished using 800-2000 mesh sandpaper. The purpose of this step is to remove the oxide scale produced on the coating surface during the APS coating preparation and wire cutting process. In addition, polishing with 800-2000 mesh sandpaper can make the coating surface flat and smooth, which is convenient for subsequent electrochemical characterization. Since the porosity of the coating needs to be calculated, a polishing machine is used to polish the coating after sandpaper polishing. The surface morphology of the polished coating is analyzed by SEM, and the porosity of the coating is calculated based on this.

[0045] Electrochemical characterization: The treated coating was used as the working electrode, Hg / HgO as the reference electrode, and the carbon rod electrode as the counter electrode. The working electrode, reference electrode, and counter electrode were placed in a standard three-electrode electrolytic cell with 1M KOH, with the coating surface of the working electrode facing the counter electrode. The oxygen evolution performance of the coating was tested using an electrochemical workstation (CHI640E).

[0046] See Figure 1 The microscopic morphology and porosity calculation diagram of FeCoNi-Ni3C oxygen evolution coating catalyst before oxygen evolution reaction observed under scanning electron microscope show a typical thermal spray coating structure. The coating porosity was measured by Image software and was about 22.1%. After the oxygen evolution stability test, it was found that a certain amount of oxidation products were generated around the pores on the coating surface.

[0047] See Figure 2 , Linear sweep voltammetry (LSV) curves of oxygen evolution of FeCoNi-Ni3C oxygen evolution coating catalyst before and after stability test. LSV overpotential of FeCoNi-Ni3C oxygen evolution coating catalyst doped with 50% Ni3C at 10mA cm-2 At a current density of 1.34 W, the oxygen evolution overpotential is only 212 mV. The overpotential performance corresponding to the LSV curve shows that the prepared coating has excellent oxygen evolution performance.

[0048] See Figure 3 , is the double layer capacitance (Cdl) of the FeCoNi-Ni3C oxygen evolution coating catalyst doped with 50% Ni3C, which reflects the activity of the catalyst. The double layer capacitance of the prepared coating is 162.68 mF cm -2 The higher double-point capacitance indicates that the prepared coating can provide more active sites to promote the OER reaction. The specific test results are shown in Table 1.

[0049] Table 1

[0050]

[0051] It can be seen from Table 1 that when the atomic ratio of Ni3C in FeCoNi-Ni3C is 50%, the overall porosity of the coating can reach 22%. This feature ensures that the coating can provide a larger surface area and more active sites to promote OER performance during electrochemical measurements.

[0052] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst, characterized in that: The following steps are involved: S1. Mixing FeCoNi powder and nickel-coated graphite Ni3C powder and then ball milling to obtain FeCoNi-Ni3C powder, wherein the atomic ratio of Ni3C in the FeCoNi-Ni3C powder is 25% to 75%; S2, using sodium hydroxide alkaline cleaning solution to remove oil stains on the surface of the metal substrate, and then using ultrasonic cleaning; S3, sandblasting the surface of the metal substrate until the roughness of the surface of the metal substrate is Ra5.5μm~Ra6.5μm; S4. Plasma spraying is performed on the surface of the metal substrate after sandblasting using FeCoNi-Ni3C powder to obtain a FeCoNi-Ni3C oxygen evolution coating catalyst with a thickness of 400 to 500 μm.

2. The method for preparing the nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst according to claim 1, characterized in that: In the step S1, glass balls are used for ball milling, the diameter of the glass balls is 4 mm-10 mm, the ball-to-powder ratio is 4:1, the speed of the ball mill is 1200 rad / min-1600 rad / min, and the ball milling time is 18 h-22 h.

3. The method for preparing the nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst according to claim 1, characterized in that: In the step S1, the particle size of the FeCoNi powder is 300-400 mesh, and the powder is a spherical powder; the particle size of the nickel-coated graphite Ni3C powder is 300-400 mesh, and the powder is a flake powder.

4. The method for preparing the nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst according to claim 1, characterized in that: The metal substrate is one of copper, copper alloy, aluminum, aluminum alloy and stainless steel.

5. The method for preparing the nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst according to claim 1, characterized in that: In the step S2, the mass percentage of the sodium hydroxide alkaline washing solution is 4.0% to 5.0%, and the metal substrate is immersed for 3.0 minutes to 5.0 minutes at a temperature of 60° C. to 70° C. to remove oil stains on the surface of the metal substrate.

6. The method for preparing the nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst according to claim 1, characterized in that: In the step S3, the surface of the metal substrate is sandblasted using white corundum abrasive particles of 180-200 meshes, the sandblasting angle is 75°-85°, the pressure of the compressed air is 0.56MPa-0.60MPa, and the sandblasting distance is 80mm-110mm.

7. The method for preparing the nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst according to claim 1, characterized in that: In the step S4, the plasma spraying process parameters are: welding current 650A-700A, voltage 42V-45V; spraying speed is 1800mm / min-2000mm / min, spraying distance is 150mm-180mm, powder output of powder feeding pipe is 10mg / s-15mg / s, powder feeding machine speed is 0.55rad / min-0.7rad / min, powder feeding gas is argon, powder feeding gas flow rate is 38psi-42psi, shielding gas is argon, shielding gas flow rate is 42psi-46psi, combustion-supporting gas is hydrogen, gas flow rate is 8psi-12psi.

8. A nickel-coated graphite-doped FeCoNi oxygen evolution coating catalyst prepared by the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Metallographic detection method for flame sprayed NiCrAl / NiC coating

    CN102798591A

  • FeCoNi-based amorphous alloy and application thereof

    CN111057969A